Synthesis and photocatalytic evaluation of 2D MoS2/TiO2 heterostructure photocatalyst for organic pollutants degradation - Kumar U.; Sinha I.; Mishra T. (My University, 2025)
This study presents a successful method for synthesizing a 2D MoS2/TiO2 nanocomposite through hydrothermal synthesis. The amount of MoS2 in the composite was 5-10 wt% to optimize the heterojunction formation to enhance the photocatalytic degradation of the organic rhodamine under visible light. The prepared samples were characterized using X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive X-ray spectroscopy (EDX), UV-diffuse reflectance spectroscopy (UV-DRS), and Fourier transforms infrared spectroscopy (FTIR) techniques. High-resolution TEM imaging confirmed the successful exfoliation of few-layer MoS2 nanosheets with lateral sizes ranging from 200 to 800 nm. Based on the results obtained, it was determined that the most effective loading of MoS2 was 5.0 wt% for achieving efficient rhodamine photodegradation under UV-visible light, outperforming both the ten wt. % MoS2 loading and pristine TiO2. The present study highlights the superior photocatalytic performance of the 5.0 wt% MoS2-TiO2 nanocomposite can be attributed to proper heterojunction formation and enhanced charge transfer leading to delayed recombination. Copyright © 2023 Elsevier Ltd. All rights reserved.